The impact of obesity related websites on decision making among students in Saudi Arabia - Ahmed I. Albarrak; Rafiuddin Mohammed; Nasriah Zakaria; Lujain M. Alyousef; Noura B. Almefgai; Hend D. Alqahtani; Hanan S. Alamer; Ahlam A. Alsulaiman (Elsevier, 2016)
Background & Objectives: The present study was to investigate the use of the internet among university students accessing obesity health information and further to measure their satisfaction and in decision-making. Methods: A cross sectional study, among students at King Saud University (KSU), Riyadh, Saudi Arabia. This study received ethical clearance from Institutional Review Board, College of Medicine, KSU. Female and male of undergraduate and postgraduate, enrolled through a random sampling. The survey questionnaire was self-administered and consisted of two sections. Results: A total of 448 students (177 males and 271 females) participated in this study. The response rate was 66.86. The study showed that the prevalence of overweight and obesity was more common among male compared to female students. Majority of the students (58.7%) were of normal Body Mass Index (BMI). It also revealed that 187 (41.7%) reported always acquire obesity health information from the internet whereas 203 (45.35) sometimes use the internet. Half of the respondents reported using a search engine to seek information. Forty-five percent reported spending at least an hour per week. Nearly 52.2% of participants are taking decision related to their lifestyle and showed statistical significant (P = 0.0001). More than half of the students believed that the obesity information in the websites are very useful. Furthermore, 84.4% reported, language presented in the websites are easy to understand. With respect to quality, 46.9% rated as excellent whereas 39.5% as average. Interpretation & Conclusions: The present study findings have demonstrated that university students are using internet in higher rates for finding obesity health information and are satisfied with the decision they are making. Finally, the study concludes that the internet online health information considered as an essential tool for health promotion among student population regarding weight control or managing obesity.